ANALYSIS OF DURABLE CRACKING AND STRUCTURE OPTIMIZATION OF REAR SUB-FRAME - ZHOU DeSheng; WU YiDong; HU HaoJu; WANG ZhenFeng (Jixie qiangdu)
In order to improve the durability of the rear sub-frame structure, a bench endurance test was carried out. Weld performance analysis was carried out for cracking in the test, the results showed that non-weld fatigue caused cracking. Through the endurance simulation analysis of the bench, the dangerous area of the original structure was found, and three optimization schemes was proposed. The performance requirements of each scheme are compared, and bilateral full welding is the best improvement scheme. The improved structure satisfies the durability test of the sub-frame bench, the endurance test of the vehicle’s twenty-four channels and four columns, and also shows that the simulation analysis method and improvement scheme are credible.